Z-score Analysis for Financial Stability on Real Estate Companies in the Indonesian Stock Exchange - Herry Santoso (Jurnal Proaksi, 2025)
Main purpose: This study empirically investigates the influence of Profitability (PRFT), Leverage (LEVG), Liquidity (LIQD), Firm Age (FAGE), Interest Rate (INTR), Firm Value (FVAL), Firm Size (FISZ), and the COVID-19 pandemic (COVD) on the Financial Stability (FSTA) of real estate companies listed on the Indonesia Stock Exchange during the period 2012–2022.